Analysis of user motivation and user interface toward screen addiction / Syahrini Shawalludin ... [et al.] - Shawalludin, Syahrini; Sanmugam, Mageswaran; Abdul Rabu, Siti Nazleen; Mohamed, Hasnah (Universiti Teknologi MARA, Kedah, 2023)
In the last decades, a great deal of research has been done on the interaction between people and digital technology. Every corporate and public company is now impacted by modern digital technologies including social media, business analytics, the Internet of Things, big data, advanced manufacturing, 3D printing, cloud and cyber-solutions, and MOOCs. Digital technologies have been thoroughly researched in both academia and business. One of the technologies that young people employ is playing digital or video games, which are played by millions of adolescents and young adults worldwide. The popularity of the impact of playing video games on people's everyday lives has increased significantly in recent years, along with the video game industry. The research aim was to assess the connection between user motivation and user interface to comprehend its effects on a student population. To carry out this study, a questionnaire was distributed to tertiary students at Universiti Teknologi MARA Kedah Branch in Malaysia who were enrolled in a variety of programmed and courses. User motivation and user interface, specifically in relation to video game analysis, are the main elements used in this research. According to the results of the analysis, there is a significant correlation between user motivation and user interface, which underlies the current rise in screen time due to technology and has been linked to mental health issues. Therefore, a special recommendation for game-based learning in reducing screen addiction may derive from a better understanding of the function of user motivation and user interface.